Palliative Therapies for Congenital Heart Disease with Ductus Dependent Pulmonary Circulation - Yuan, Shi-Min (Zeitschrift für Geburtshilfe und Neonatologie, 2017)
In neonates, the management of ductus dependent pulmonary circulation is challenging. There have been three palliative therapies for this lesion: the modified Blalock-Taussig shunt, ductal stenting and prostaglandin E infusions, for maintaining the ductal patency before definite operations. Debates remain with regard to the indications and disadvantages of three palliative therapies. The aim of this article is to give a brief review of these three palliative therapies.
Keywords: congenital heart defects; ductus arteriosus; pulmonary circulation.